AI In Telemedicine (International Journal of Scientific Research and Management (IJSRM), 2023)
Telemedicine has potentially witnessed a notable growth during the recent years, specifically driven by technical advancements, a globalised impact that Covid-19 pandemic had as well as evolution in the healthcare needs [1]. Telemedicine powered by AI necessarily integrates the likes of Machine Learning (ML), computer vision as well as Natural Language Processing (NLP) in order to bring notable improvement to the patient care by allowing remote forms of diagnostics, personalized treatment plans as well as predictive analytics. This paper mainly highlights the role of AI in the field of Telemedicine along with its contained potential intended to bridge the gaps when it comes to Healthcare Access & Quality.